Estimation of Daytime NO3 Radical Levels in the UK Urban Atmosphere Using the Steady State Approximation Method. (29th July 2015) - Khan, M. A. H.; Morris, W. C.; Watson, L. A.; Galloway, M.; Hamer, P. D.; Shallcross, B. M. A.; Percival, C. J.; Shallcross, D. E.
Abstract : The steady state approximation has been applied to the UK National Environment Technology Centre (NETCEN) data at three urban sites in the UK (Marylebone Road London, London Eltham, and Harwell) over the period of 1997 to 2012 to estimate the concentrations of daytime NO3 . Despite the common assertion that NO3 levels are negligible in the day as a consequence of photolysis, there are occasions where NO3 reaches a few pptv. A seasonal pattern in NO3 concentration was observed with higher levels in the spring with consistent peaks in April and May. A combination of temperature effects (the formation of NO3 from the reaction of NO2 with O3 has a high activation energy barrier), a distinct pattern in O3 concentration (peaking in spring), and loss via reaction with NO peaking in winter is responsible for this trend. Although reaction with OH is still the dominant loss process for VOCs during the day, there are VOCs (unsaturated) that will have an appreciable loss due to reaction with NO3 in the daytime. Since the addition reaction of NO3 with alkenes can lead directly to organic nitrate formation, there are implications for O3 formation and secondary organic aerosol formation during daytime and these are discussed.